Potential of two-stage cultivation in microalgae biofuel production. (15th September 2019) - Nagappan, Senthil; Devendran, Saravanan; Tsai, Pei-Chien; Dahms, Hans-Uwe; Ponnusamy, Vinoth Kumar
Graphical abstract: Abstract: Microalgae are a group of microorganisms considered to be a potential source of next-generation biofuel owing to high photosynthetic rate. However, biofuel compounds including lipid, carbohydrate, and hydrogen are not sufficiently produced by microalgae under normal conditions; therefore economical viability of microalgal biofuel production has not reached the ultimate stage of commercial viability. In order to overcome the above limitation, various stress conditions have been applied on microalgae to boost lipid, carbohydrate and hydrogen production. Even though stress conditions increases the production of biofuel compounds, microalgae growth is severely affected. In this regard, a two-stage cultivation mode wherein first stage involving high biomass production under media optimized heterotrophic condition and second stage involving lipid, carbohydrate and hydrogen accumulation under stress integrated phototrophic mode is considered as a potential route for biofuel production in microalgae. The present review critically evaluates various two-stage strategies adopted in microalgal biofuel production by comparing lipid, carbohydrate and hydrogen productivities with that of single stage cultivation. In addition, advantages of two-stage cultivation including co-product generation, less bacterial contamination, improved biodiesel quality, auto-flocculation, and bioremediation potential are also discussed. Finally, the paper summarizes the two-stage cultivation modes by identifying the bottlenecks and suggesting the future potentialities of the process.